Experiences of siblings of people with intellectual disabilities: Multiregional perspectives. Issue 2 (5th November 2021) - Paul, Alicia M.; Hussey, Meghan M.; Woodman, Ashley C.; Smith, Ashlyn L.; Shriver, Timothy P.
Abstract: Objective: This study described the benefits, challenges, and support needs of siblings of people with intellectual disabilities in Latin America, Africa, and Asia‐Pacific. Background: Growing up with a sibling with an intellectual disability can influence young people in various ways. Previous research has focused primarily on Western contexts and the use of parent rather than sibling perceptions. Method: Twenty‐two siblings of people with intellectual disabilities between ages 8 and 25 years participated in three semistructured focus groups during Special Olympics Regional Sibling and Family Workshops. Participants discussed their personal experiences and perceived support needs. Transcripts were coded for themes and subthemes using an iterative process. Results: Thematic analysis revealed positive themes related to valuing siblings with intellectual disabilities, close relationships, and personal growth. Challenging themes found were related to the self, family, and broader community. For supports needed, themes included future planning and services for siblings with intellectual disabilities. Conclusion: Siblings from these regions described their experiences as a combination of benefits and challenges, noting the distinct influence of stigma on their relationships and the need for higher quality services. Implications: Findings point to a need for a whole‐family‐centered approach to support siblings of people with intellectual disabilities in the Global South.